(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper presents a comparative analysis of the Indian and Western family systems from the perspective of social philosophy. Drawing upon scholarly literature, the study explores philosophical foundations, structural characteristics, cultural roles, and evolving trends within both systems. The Indian family system is examined through its collectivist orientation, rooted in concepts such as Dharma and the Āśrama life stages, while the Western family system is considered through its emphasis on individualism, autonomy, and liberal values. A comparative framework highlights differences in structure, decision-making, gender roles, and adaptability, as well as converging influences under globalisation. This research underscores the value of balancing communal solidarity with personal autonomy in contemporary society.